What can regular and timely student feedback tell us about the teaching and learning processes?. Issue 6 (2nd November 2017) - Youssef, Lamiaa S.
Abstract: Most studies on the evaluation of teaching focus on the input (teacher traits) or the output (student-generated products) of the teaching and learning processes. This article is based on a case study that examines the three components of teaching and learning: input, output and process. It presents a framework for collecting quantitative and qualitative data on the quality of instruction, assessment and feedback, and learning environment in college composition courses to complement the feedback provided by the end-of-course student evaluations of teaching for the purpose of monitoring, guiding, and improving instruction.